Utilização da modelagem computacional para avaliar a influência das planícies de maré na hidrodinâmica de regiões estuarinas - Côco, Kátia Muniz (2010)
Along coastal areas have suffered considerable environmental degradation caused by increasing pressure on the natural marine resources. An important tool used to support decision-making in environmental management of a water body is the computational modeling of the hydrodynamic conditions of flow and water quality. One of the most important physical phenomena for the hydrodynamics of estuaries is the tide that spread from the ocean to estuarine regions, suffer distortions that can be represented by non-linear growth of constituent compounds and harmonics of the main constituents of the astronomical tide. The asymmetries in the tides cause differences in the duration of the flood and ebb tide vertical, resulting in systems where the current flood (or ebb tides) may dominate on the ebb (or floods). These characteristics can be represented by the parameters a/h (tidal height / depth of the channel) and Vs/Vc (volume of storage intertidal/ channel volume in mean sea level). Thus, we carried out computer simulations in this study, using the mechanism of flooding and drying in porous media of SisBaHiA®in idealized estuary with the aim of evaluating the influence of tidal flats in the dominance of chains. Tests showed no presence of tidal flats, in which the phenomena of friction with the bed stand, tend to be dominated by the flood. Already the presence of estuaries with tidal flatstend to be dominated by the ebb. It was observed also that the asymmetry of the tides are intensified when the tidal flats when the tide rise and penetrates into the head of the estuary.